The development of interview protocol to explore hybrid agile software development phase - Yahya, Norzariyah; Maidin, Siti Sarah; Safar, Muhammad Shukri (International Journal of Advanced Trends in Computer Science and Engineering, 2021)
Agile practices are a development approach based on agile manifestos that value individuals and interactions, working software, customer collaboration and responding to change. Recently, Software Engineering (SE) team is combining agile with non-agile development approaches, which lead to hybrid agile. Hybrid agile is a mixture of a plan-driven development approach and agile practices. Hybrid agile has gained the interest of software engineering team as one of the development approaches for recent software development projects. However, there are uncertainties of security measures of hybrid agile. Therefore, the security strategies of a software project developed based on hybrid agile needs further investigations. This research is a proportion of a study on hybrid agile, in which this research focuses on the development of the data collection instrument to study hybrid agile. This research explores the development and validation of an interview protocol that will be the instrument for studying the hybrid agile approaches and methods implemented by the Software Engineering team and discovering the security strategies taken to ensure reliable software will be deployed to the end-users. This paper will discuss the questions designed for research, which involves the development of the interview protocol. This paper also explains the validation process and reliability examination of the interview protocol to ensure the interview protocol is reliable for the actual data collection process from the identified sample population.